2010
DOI: 10.1063/1.3503587
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashallow Ohmic contacts for n-type Ge by Sb δ-doping

Abstract: We demonstrate ultrashallow Ohmic contacts for n-Ge by the Sb δ-doping and low-temperature Ge homoepitaxy. We find that the segregation effect of Sb on Ge(111) is lower than that on Ge(100) for growth temperatures below 400 °C. Consequently, we achieve the δ-doping for Ge(111), having very high concentrations above 1020 cm−3 and abrupt profiles within nanometer-scale widths. By introducing the δ-doping to atomically controlled metal/Ge Schottky contacts, completely symmetric current-voltage characteristics, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 19 publications
3
39
0
Order By: Relevance
“…It was also stated in the report that the shift of the temperature dependence curve of the segregation length toward lower temperature region is well explained by the decrease of the thermal activation energy rather than by the increase of the segregation energy within the framework of the two-state model. The lower thermal activation energy calculated for Ge (100) than that for Ge (111) corresponds directly to the experimentally observed temperature dependence curve for Ge (100) in the lower temperature region as compared with that for Ge (111) [7]. Unfortunately there are very few experimental data on surface segregation behaviors of other dopant atoms on Ge (100) and Ge (111) surfaces, we cannot compare our computational results directly with the experimental data.…”
Section: Resultsmentioning
confidence: 38%
See 1 more Smart Citation
“…It was also stated in the report that the shift of the temperature dependence curve of the segregation length toward lower temperature region is well explained by the decrease of the thermal activation energy rather than by the increase of the segregation energy within the framework of the two-state model. The lower thermal activation energy calculated for Ge (100) than that for Ge (111) corresponds directly to the experimentally observed temperature dependence curve for Ge (100) in the lower temperature region as compared with that for Ge (111) [7]. Unfortunately there are very few experimental data on surface segregation behaviors of other dopant atoms on Ge (100) and Ge (111) surfaces, we cannot compare our computational results directly with the experimental data.…”
Section: Resultsmentioning
confidence: 38%
“…One of the crucial problems associated with the fabrication of aggressively scaled Ge channel CMOS is the formation of n-type ultrashallow junctions with ion implantation techniques [5][6]. It was recently reported that the formation of ultrashallow ohmic contacts for n-type Ge was made possible by Sb -doping followed by Ge homoepitaxial growth [7]. It was also shown that the segregation effect of Sb on Ge (111) surface is lower than that on Ge (100) surface.…”
Section: Introductionmentioning
confidence: 99%
“…e l s e v i e r . c o m / l o c a t e / t s f an n + -Ge(111) layer consisting of Sb δ-doped layer (n~10 14 cm −2 ) and a 5-nm-thick Ge epitaxial layer was grown by molecular beam epitaxy (MBE) at 400°C [17]. Here, in order to increase the interface resistance of the Schottky-tunnel barrier, the doping density of Sb was controlled by changing the growth time.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…By fabricating an atomically controlled metal/Ge interface [12][13][14][15][16] and using an ultra-shallow Sb-doping technique [17], we have addressed other spin injection and detection technologies without using the insulating tunnel barriers. So far, we have demonstrated an electrical detection of spin accumulation created in an n-Ge channel through Fe 3 Si/n + -Ge Schottky tunnel contacts [18].…”
Section: Introductionmentioning
confidence: 99%
“…In general, electrical properties of such interfaces are dominated by the Fermi-level pinning phenomena [64][65][66] and doping conditions. 67,68) By carefully tuning these conditions, the LSVs were fabricated, as shown in Fig. 9(a), where an Sb δ-doped layer (∼1.0 × 10 14 cm…”
Section: Lateral Spin Valves With Heusler Alloysmentioning
confidence: 99%